Gender and Natural Resources in Siberia, Costa Rica - Rodríguez, Mayra (2006)
The research identified the perceptions that men and women of the community of Siberia –south of Costa Rica- have about the male and female roles in regard to Natural Resources. The 53 study samples consisted of different age groups of both men and women: children, adolescents, adults and seniors. The most important findings, were that the perceptions of  each study group were similar, regardless of their sex or age.  The interpretation of the participants regarding the study’s variable, is that the role of men towards Natural Resources is much more active than women’s; they are considered to be more in   touch   with   resources,   much   more   responsible   of   their deterioration,  more  obliged  to  take  care  of  nature  and  almost completely in charge of thinking and developing new ways to use Natural Resources, in a friendly environmental way.